Vocational guidance and career development in cultural institutions of the secondary vocational education in china - Sergey Sergeevich Zengin (Вестник Майкопского государственного технологического университета)
At present, vocational guidance and career development are the most important aspects of training qualified personnel ready to work in modern conditions. In this regard, the issue of studying the best world practices becomes relevant. Changing the economic model of the People's Republic of China leads to the process of reforming the secondary vocational education system (SVE), the search for ways to train qualified personnel more effectively. The purpose of the research is to study the experience of the secondary vocational education system of the PRChina in the field of career guidance. The research problem is the need to identify and analyze merits and demerits of vocational guidance and career development in the cultural vocational education and training system of China in order to assess borrowing of best practices and increase the efficiency of qualified personnel training in Russia. The research methods used are study and analysis of the regulatory framework, scientific literature, transcripts, direct acquaintance with the system of training mid-level specialists in the field of Chinese culture and a comparative analysis of materials. The article highlights the factors affecting the reform of the SVE system in China, and the features that determine the vector of development of this level of training for the development of socio-economic and political life of the country. According to the results of the study, we can conclude that the system of career guidance and career development is based on a solid political and ideological foundation. There are special services for career guidance and career development in educational institutions, the curriculum contains relevant disciplines. The most important principle of a specialist training is formation of social responsibility in his mind.